Evolution of Parenting Dynamics in Families Within Stunting-Locus Area - Erma Kusumawardani; Lathifa Ellen; Amanda Adityaningrum (Universitas Negeri Semarang, 2025)
Background: Stunting cases in developing countries are a challenge to date, stunting has an impact on the quality of human resources in a country. Research Urgency: Stunting given its numerous effects, including its substantial short-term effects on children's brain development, physical growth, and metabolism, stunting's urgency becomes clear. Although the short-term consequences are alarming, the long-term consequences may include diminished cognitive function, compromised immunity, poorer academic achievement, and an increased risk of long-term conditions like diabetes, high blood pressure, and obesity. Research Objectives: This research aims to describe the role of Posyandu cadres in stunting focus locations and the changes in parenting styles that parents make after learning their child is at risk of stunting. Research Method: This study uses a qualitative approach with a case study design. Purposive sampling was employed, and seven participants were selected, consisting of mothers of children under five at risk of stunting, Posyandu cadres, and the Head of Village. Data collection involved observations, in-depth interviews, and documentary analysis. The data analysis included data reduction, presentation, and conclusion drawing. To ensure data validity, both source triangulation and technique triangulation were used. Research Findings: The role of Posyandu cadres in addressing stunting includes being instructors, record-keepers, and motivators, and the changes in parenting styles observed are from permissive and neglectful styles to democratic styles. Research Conclusion: The results of the study provide meaning to informal education that has a wide scope. This is proven by the efforts to prevent stunting carried out by posyandu cadres to encourage changes in parenting patterns of parents who have children at risk of stunting.. Research Novelty/ Contibution: This study encourages in-depth research related to stunting prevention efforts through education for parents which must be carried out with various special strategies with an adult learning approach. Because not all posyandu cadres have the same understanding in providing education.